From Basic to Clinical Practice in Internal Medicine - Ika P Wijaya (Interna Publishing, 2016)
Acta Medica Indonesiana, today is The Indonesian Journal of Internal Medicine, addresses all the concerns of science on Internal Medicine. In this edition, we publish a study conducted by Putra ST.1, a cohort retrospective study on teenager subjects who were breast-fed as infants and the effects on the development of atherosclerosis. This study supported the idea that breastfeeding may have protective effect on the development of atherosclerosis. We publish the study since it included the health issues of teenagers. We also publish a study from Yogyakarta conducted by Hartopo AB, et al. which found that neutrophil to lymphocytes ratio of more than 6.2 is correlated to the increased in-hospital adverse events. The subjects were patients with ST elevation myocardial infark (STEMI). Based on the results of the study, the neutrophil/ lymphocyte ratio can be utilized as a predictor of adverse events in patients with STEMI.